Filogenetik Bulu Babi Tripneustes gratilla menggunakan Gen Sitokrom Oksidase Subunit 1 - Nurul Abidin; Rina A. Mogea; Robi Binur (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
Sea urchin Tripneustes gratilla is multifunction organism that can be used as potential food source because of its high nutrient content. This organism can also be utilized bioindicator of sea waters and as a modal of organism for studying biology’s purposes. The purposes of this research is studying Filogenetic of sea urchin T. gratilla from waters of Wasior and Serui. The research has been doing at the Biotechnology Laboratory of the state of University of Papua on November to December 2009. The sample was extracted by using Chelex 10 % and was amplified with PCR technic (polymerase chain reaction). Sequencing of CO I gens (cythocrome oxidase subunit I) was done using sequencher ABI 377 (Apllied Biosystem). The result of nucleotid sequence data was analyzed utilizing MEGA 4.0.2. This researchs result showed that the gen fragment that was succesfully amplified 601 bp. The sequence result of nucleotid which was analyzed the variaty of nucleotid between the sample from two waters. Filogenetic analyzing toward individu of the two waters produce the two clusters. The first cluster consist of SER 01 and sub cluster which is consisted of WSR 02 and SER 02. While, the second cluster consist of only WSR 01. This result showed that every individu from Wasior (WSR 02) has close genetic relation with other individu from Serui (SER 02), that proved there is genetic flow between the two waters.